EVALUATING MAXIMUM COMPENSATION CRITERIA FOR PROPERTY DEVELOPERS ACCORDING TO THE INTERIM REAL PROPERTY REGISTER IN DUBAI (UUM Journal of Legal Studies, 2021)
This paper presents an assessment of the criteria for setting the maximum amount of compensation given to a property developer when a buyer breaches their contractual obligations according to the law of the Interim Real Property Register in the Emirate of Dubai. The register gives the developer the power to deduct a certain percentage of the amount paid to them by the buyer, without the need to resort to justice or arbitration. Such a power is one of certain exceptional powers granted to the developer under this law to encourage property investment in Dubai. This research aims to define the type of compensation that the property developer deserves, as well as present the criteria for the maximum amount of compensation and an evaluation of them. This was achieved by analyzing Article 11 of the mentioned law for accuracy and fairness on this issue, and its success in balancing the conflicting interests of both parties. One key result found was that the legislator had not succeeded in balancing the two parties of the off-plan sale. It is strongly recommended that the legislator abolish the three criteria on the maximum amount of compensation and adopt alternative criteria.